BRAZILIAN AIRPORTS NETWORK EVALUATION - PEREIRA, DEIVISON DA SILVEIRA; SOARES DE MELLO, JOAO CARLOS CORREIA BAPTISTA (Brazilian Journal of Operations & Production Management, 2020)
Goal: This paper presents an analysis of the Brazilian air network based on the measure of h centrality. Design / Methodology / Approach: The purpose of this study is to define and determine the central network using the concepts of h-centrality. Method adapted from graph theory concepts with bibliometrics, especially the h-index. From the center of this index will be listed the most used airports to define the Brazilian central network and thus determinate the type h-index of Brazil. Results: The main airports in the results represent more than 50% of the homologated flights in Brazil. Practical implications: This model of air flight frequencies assists in public policy guidelines and planning both in air traffic control and in the verification of system impacts. Originality / Value: The method seeks to provide the list with main important airports without any prior definition by a decision maker.